Long-term low-dose aspirin promotes laser-induced choroidal neovascularization through suppressing TSP-1 expression - Yi, Caijiao; Luo, Chang; Zhao, Jiawu; Roubeix, Christophe; Lechner, Judith; Penalva, Rosana; Yang, Nan; Liu, Jian; Wang, Qichang; Chakravarthy, Usha; Sennlaub, Florian; Chen, Mei; et al. (Frontiers in Cellular Neuroscience, 2025)
PurposeTo investigate the impact of low-dose, long-term aspirin use on neovascular age-related macular degeneration (nAMD).MethodsAdult C57BL/6J or Thbs-1–/– mice were treated with daily aspirin (1.25 mg/kg) for 8 weeks before being subjected to laser-induced choroidal neovascularization (CNV). The animals were left for 7–10 days with continued aspirin use before the eyes were collected for further investigations. Bone marrow-derived macrophages (BMDMs) and primary retinal pigment epithelial (RPE) cells were treated with different concentrations of aspirin (1, 10, 100 μM) for two days before being subjected to LPS+IFNγ for 16 h. The expression of cytokine genes was evaluated by qRT-PCR. The concentrations of thrombospondin-1 (TSP-1) were measured by ELISA.ResultsAspirin treatment did not affect circulating immune cell profiles in normal mice but significantly increased CD11b+ cells in laser-induced CNV mice. The treatment significantly increased the severity of laser-induced CNV and reduced serum levels of TSP-1. In vitro aspirin treatment upregulated Tnfa and Ccl22, down-regulated Thbs-1 mRNA expression, and reduced TSP-1 production in LPS+IFNγ-treated M1 BMDMs but not RPE cells. Thbs-1–/– mice developed severe laser-induced CNV, which was not affected by aspirin intervention. nAMD patients had significantly lower serum levels of TSP-1 than healthy controls, although no significant difference was found between nAMD patients with and without aspirin use.ConclusionLow-dose long-term aspirin use promoted the severity of laser-induced CNV by down-regulating TSP-1. Lower serum levels of TSP-1 may be a risk factor for nAMD. The long-term ocular safety of aspirin should be validated in prospective cohorts.